Interactions between HLA-G and HLA-E in Physiological and Pathological Conditions - Morandi, Fabio; Pistoia, Vito (Frontiers in Immunology, 2014)
HLA-G and HLA-E are immunoregulatory molecules that belong to HLA-Ib family. The role of these molecules in the control of the immune response has been extensively analyzed, both in physiological and pathological conditions. We have here summarized data present in the literature regarding the interaction of these molecules in different settings. These data suggested that HLA-G and –E co-operate in physiological conditions (i.e. establishment of an immune tolerance at maternal/fetal interface during pregnancy), whereas their role in the course of tumors or autoimmune/inflammatory diseases may be different or even opposite. Future studies aimed at investigating the interaction between HLA-G and HLA-E will help to clarify mechanism(s) underlying the regulation of immune effector cells in health and disease.